A self-penetration torpedo anchor with vibrational shearing. (15th September 2021) - Chen, Xiaohui; Zhang, Minxi; Yu, Guoliang
Abstract: As the depths at which marine facilities are constructed increase, mooring systems have become more complex, expensive, and difficult to install, making it necessary to develop new types of anchors to replace conventional drag-type anchors. In this paper, a new anchor concept based on the application of sediment fluidization technology is proposed. The proposed self-penetration torpedo anchor has a design similar to that of a torpedo anchor but is equipped with a specially designed mechanical vibrational unit. Laboratory tests were carried out to assess the penetration behavior, holding performance, and pullout behavior of the proposed torpedo under self-induced vibration. To evaluate the effect of installation on the anchorage force, the anchoring forces were measured over different rest times following vertical arrival at designated penetration depths. It was demonstrated that the anchor is able to automatically enter deep beds at moderate penetration speeds and that it has a high holding index, with an anchoring force that can recover more than 83.2% of its holding capacity following 7 d of rest in a silty bed with median particle diameters d50 of 31 μm. Furthermore, unlike conventional torpedo anchors the anchoring force and penetration depth of the self-penetration torpedo anchor are not limited by water depth or drop height. Because the proposed torpedo can be more easily extracted through the application of vibration, problems arising from an inability to pull the anchor out can be more readily avoided. Highlights: A deep penetration can be achieved by reducing the resistance of the seabed soil to the anchor induced by mechanical vibrations. The application of self-penetration anchor is independent of water depth or anchor drop height. The self-penetration torpedo anchor has a high holding index at arbitrary water depth. The application of mechanical vibrations also eases the recovery process of the self-penetration torpedo.